2022
DOI: 10.3389/fbioe.2021.803868
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Primary Pulmonary Angiosarcoma With Brain Metastasis

Abstract: Primary pulmonary angiosarcoma (PPA) is a rare malignant vascular tumor, of which early diagnosis is challenging due to lack of specific clinical manifestations and a low level of suspicion. Here, we report a case of PPA presented with advanced brain metastasis. A 21-year-old patient with 1 week history of headache and mild cough was hospitalized for a head injury. Head MRI showed multiple intracranial lesions with brain edema. Chest CT displayed bilateral pulmonary infiltrates with mediastinal lymph node enla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Due to the various features of primary pulmonary angiosarcoma on CT scan, this can also be misinterpreted as an infection. Tang et al, have reported in a case that has been misdiagnosis due to the CT finding of left lower lobe ground-glass changes and lymphadenopathy especially with blood tests pointing toward that direction and their patient has been treated for tuberculosis Tang, et al [4]. PET is considered to be valuable to rule out widespread metastasis at presentation as well as for close follow-up throughout the treatment course (Wilson,et al [5]).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the various features of primary pulmonary angiosarcoma on CT scan, this can also be misinterpreted as an infection. Tang et al, have reported in a case that has been misdiagnosis due to the CT finding of left lower lobe ground-glass changes and lymphadenopathy especially with blood tests pointing toward that direction and their patient has been treated for tuberculosis Tang, et al [4]. PET is considered to be valuable to rule out widespread metastasis at presentation as well as for close follow-up throughout the treatment course (Wilson,et al [5]).…”
Section: Discussionmentioning
confidence: 99%